Renal Physiology Resources. Issue 3 (2nd July 2016) - Travis, Lisa D.
ABSTRACT: Renal physiology is the study of all functions of the kidney. There is a mnemonic, A WET BED, that helps one remember kidney functions: A) maintenance of ACID-base balance; W) maintenance of WATER balance; E) balance of ELECTROLYTES; T) removal of TOXINS; B) control of BLOOD pressure; E) production of ERYTHROPOIETIN; and D) metabolism of vitamin D. This article will highlight interactive websites and tutorials that may serve as supplemental material for teaching and learning renal physiology for allied health, nursing, and medical students.